Weak Convergence Theorems for Mixed Type Total Asymptotically Nonexpansive Mappings in Uniformly Convex Banach Spaces (Journal of Mathematical Study, 2021)
In this paper, we study a new two-step iteration scheme of mixed type fortwo total asymptotically nonexpansive self mappings and two total asymptoticallynonexpansive non-self mappings and establish some weak convergence theorems inthe framework of uniformly convex Banach spaces. Our results extend and generalizeseveral results from the current existing literature.